2019
DOI: 10.1016/j.dib.2019.104031
|View full text |Cite
|
Sign up to set email alerts
|

Data on the yield and quality of organically hybrids of tropical tomato fruits at two stages of fruit maturation

Abstract: Organic and traditional cultivation techniques significantly affect the yield and quality of tomato fruit. To achieve the highest possible production of hybrid lines, the appropriate cultivation system is needed. The application of different cultivation systems was expected to improve the yield and fruit quality of three new tropical hybrid tomatoes varieties that prolong fruit shelf life. This experiment was conducted to identify the effect of the different cultivation systems on the yield and fruit quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Unfortunately, it has been documented that tomato plants under organic farming undergo moderate environmental stress [ 11 ], causing lower fruit yields [ 12 , 13 , 14 , 15 , 16 ], a reduction in fruit weight and firmness [ 14 , 16 ], and an increase in phytopathogen infections [ 9 , 17 ], compared to conventional production systems. Interestingly, it has been suggested that a potential cause of the agricultural problems observed in organic production could be associated with alterations of the tomato plant microbiota [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it has been documented that tomato plants under organic farming undergo moderate environmental stress [ 11 ], causing lower fruit yields [ 12 , 13 , 14 , 15 , 16 ], a reduction in fruit weight and firmness [ 14 , 16 ], and an increase in phytopathogen infections [ 9 , 17 ], compared to conventional production systems. Interestingly, it has been suggested that a potential cause of the agricultural problems observed in organic production could be associated with alterations of the tomato plant microbiota [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%